Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne; Beaulieu, Denise (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)
Ce rapport présente les constats qui ressortent de l’étude sur les besoins spécifiques des femmes immigrantes francophones dans les communautés francophones en situation minoritaire (CFSM) de quatre provinces et un territoire (P/T) du Canada : Colombie-Britannique, Manitoba, Nouvelle-Écosse, Ontario et Yukon. Cette étude a été réalisée dans le cadre du projet Intégration des nouveaux arrivants dans les communautés francophones au pays, porté conjointement par l’Alliance des femmes de la francophonie canadienne (AFFC), la Commission nationale des parents francophones (CNPF) et la Fédération des aînées et aînés francophones du Canada (FAAFC). Son volet femmes a pour principal objectif de favoriser une meilleure compréhension des besoins des femmes immigrantes francophones au Canada. L’étude visait à identifier les besoins des immigrantes francophones ayant choisi de s’établir dans les quatre provinces et le territoire mentionnés ci-dessus, en lien avec les capacités des Réseaux d'immigration francophone et des services d’établissement à appuyer leurs efforts d’inclusion. Quelques recommandations portent sur les services de santé.
Nombre de pages: 52

Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Linguistic Minorites and Society / Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods. Interpretation: French-only speakers in Ottawa face modest — but statistically significant — overall inequities in travel burden when accessing primary care, compared with the general population, and higher inequities in specific neighbourhoods. Our results are of interest to policy-makers and health system planners, and our methods can be replicated and used as comparative benchmarks to quantify access disparities for other services and regions across Canada.

Going the distance: a cross-sectional geospatial analysis quantifying province-wide inequities in travel-based access, and fragility of access to French-language primary care provided by family physicians in Ontario, Canada - Belanger, Christopher; Timony, Patrick E; Bélizaire, Arlynn; Desilets, Antoine; Fitzsimon, Jonathan Peter; Gauthier, Alain P; Godfrey, Leanda; Karunananthan, Sathya; Kehoe MacLeod, Krystal; Muray, Mwali-Nachishali; Peixoto, Cayden; Bjerre, Lise M (BMJ Open, 2026)
Objectives Language-concordant care, or healthcare in one’s preferred language, is important both for health equity and for improving health outcomes. Linguistic minorities, like Francophones in Ontario, Canada, are at risk of poorer clinical outcomes if they receive non-language-concordant primary care. However, common ratio-based access measures can provide misleading views of minorities’ actual access levels. This cross-sectional geospatial study demonstrates a new way to measure primary care access using average travel time to the nearest five English- and French-speaking family physicians. We also introduce the concept of primary care access fragility, where a region’s primary care access may depend on one or a few local family physicians. Our research question is: are there differences in travel burden and access fragility for census subdivisions (CSDs) across language (English/French), rurality (urban/rural) and region (north/south) in the province of Ontario, Canada? Design We conducted a cross-sectional geospatial analysis to estimate English-language and French-language primary care travel burdens and access fragility in Ontario, Canada. We used population and boundary data from Statistics Canada’s 2021 census, road-network data from OpenStreetMaps, and family physician practice locations and language abilities from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Setting: We conducted our analysis for Ontario, Canada’s 577 CSDs, which correspond roughly to municipalities and with populations ranging from 5 inhabitants in Rainy Lake 17B to a high of 2 794 356 in Toronto. Participants: Using public data from January 2026, we identified 15 762 family physicians practising in Ontario, of whom 11.0% reported speaking French. Patient data were obtained from the most recent 2021 census. Primary and secondary outcome measures: Our first primary outcome measures were CSD-level mean travel time to the nearest five English-speaking family physicians, and CSD-level mean travel time to the nearest five French-speaking family physicians, which we compared to explore regional inequities in travel burden. Our secondary outcome measures were based on a novel notion of the travel burden component of ‘primary care access fragility’. This metric indicates how dependent a region’s access is on a small number of local physicians and is defined as the difference between the CSD-level mean travel time to the nearest one physician and to the nearest five physicians. As the difference in travel times grows, so too does access fragility. Results Median differences in French-language and English-language travel burdens were strongly significant across rurality, regions and overall (median difference 13.4 min, p<0.001, IQR 4.9–29.3 min), as was primary care access fragility (median difference 5.2 min, p<0.001, IQR 0.8–18.4), with larger travel burdens and fragilities in northern and rural communities. Conclusions Compared with the general public, Ontario’s French-speakers face higher travel burdens to language-concordant family physicians and higher access fragility, especially in rural and northern regions. Our results are of interest to policymakers and health-system planners, and our methods are applicable to other populations and regions.

Experiences and Perspectives of Caregivers of Francophone Older Adults Accessing Community Health Services in Toronto: an Exploratory Qualitative Study - Boyd, Elizabeth K.; Beogo, Idrissa; Liu, Barbara; Schneider, Fabien; Norris, Mireille (Canadian Geriatrics Journal, 2025)
Background Canada is a bilingual country; however, outside of Quebec, healthcare services are predominantly offered in English. With the increasing older adult population and stretched healthcare resources, Francophone older adults may face significant challenges in accessing care due to their linguistic minority status. This study explores the experiences of caregivers of Francophone older adults in the Greater Toronto Area (GTA). Methods Using a convenience sampling strategy, caregivers of patients who had undergone geriatric assessment at the Centre Francophone du Grand Toronto (CFGT) were recruited. Participants underwent 45-minute, semi-structured interviews and completed demographic questionnaires. Three independent reviewers conducted qualitative content analysis of the interview transcripts, using the socioecological model of health and NVivo12. Results Nine participants were primarily female (n=5), with age ranges of 40–49 (n=2), 50–59 (n=3), and 60+ (n=4). They originated from North America (n=5), Africa (n=3), and the Middle East (n=1); about half preferred English over French. Thematic analysis identified three key themes: 1) Barriers Accessing Health Care in the French Language; 2) The Need for Interpreter Support; 3) Importance of Comprehensive Francophone Community Services. Conclusions Despite the presence of organizations (e.g., CFGT), this study reveals a significant gap in French-language services for older adults in the GTA, leading to increased challenges for their caregivers. Due to linguistic barriers, caregivers must act as interpreters to mitigate the risks associated with miscommunication and potentially worse health outcomes. Addressing these issues requires increasing bilingual healthcare providers, enhancing funding for Francophone community services, and improving support systems (e.g., interpreters).

A Scan and Study of Primary Health Care Models for Francophone Communities in Minority Settings Accross Canada - Canadian Association of Community Health Centres et Société Santé en français (2016)
pages: 40

Qui sont les étudiantes du programme de formation francophone d’infirmières praticiennes? - Caty, Suzanne; Michel, Isabelle; Pong, Raymond; Stewart, Dianne (Ref;ets, 2007)

How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report: Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba, by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Collectif LGBTQ* du Manitoba, 2023)
Comment pallier le risque accru de discrimination ou de stigmatisation auquel font face les membres de la Communauté dans leurs recours aux services ou dans leur participation aux événements, surtout en collaboration avec des organismes non francophones ou non 2ELGBTQ+ ? En quoi consistent concrètement l’accessibilité, l’inclusion et les pratiques prometteuses concernant l’offre de services sociaux et de santé destinés aux membres de la Communauté? Et selon quels critères objectifs établir des partenariats, concevoir des services ou encore évaluer et améliorer des services existants? Le présent projet a visé à répondre à ces questions, par le biais d’un nouvel outil de diagnostic. Le présent rapport présente premièrement la démarche qui a été entreprise pour développer cet outil de diagnostic. Il présente ensuite l’outil tel qu’il s’applique aux trois volets (santé, épanouissement social et culturel, éducation). Nous passons ensuite en revue les limites du projet actuel et proposons des recommandations pour les suivis à entreprendre. Ce rapport sert donc à la fois d’outil analytique à l’état d’essai et de plan d’action pour le Collectif afin de poursuivre la mise en œuvre des recommandations du rapport « Des nôtres »
Nombre de pages: 40

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - de Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 4 - Identification of current bilingual human ressources and human resource practices - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
The first part of the comprehensive study entitled “Improving St. Boniface and St. Vital Seniors’ Access to French-language Health Services,” provided an overview of the health status and service needs of seniors in these two neighborhoods. The second part, focused on identifying available French-language health services, listed 106 public, community, private forprofit and private not-for-profit and community organizations offering Frenchlanguage services in St. Boniface and St. Vital. The goals of this fourth part of the study are to: 1) identify bilingual human resources able to serve seniors in French within these organizations across the continuum of care and 2) better understand current practices and challenges in recruiting, hiring and retaining professionals who can offer French-language services. Specifically, we will attempt to determine the number and percentage of professionals who can offer French-language services, identify the nature of services offered by these bilingual professionals, identify current practices for recruiting and hiring bilingual staff and identify the challenges in matching the needs of seniors with bilingual human resources. This will provide us with an overview of current bilingual human resources and human resource practices in designated bilingual or Francophone facilities, long-term care facilities and home care providers in St. Boniface and St. Vital.
Voir le rapport en anglais à partir de la page 36 du PDF joint.

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Providers of language-appropriate health care providers are scarce: Self-declared language capabilities of the healthcare workforce in Ontario - Demers, Chantal; Bourgeault, Ivy Lynn; Leal, Andrew; Simkin, Sarah; Sweetman, Arthur

Equity, safety & health outcomes: The case for a national minimum data standard around health workforce language data in Canada - Demers, Chantale; Richard, Lise; Bourgeault, Ivy. Lynn

La formation à distance : un moyen novateur pour promouvoir la santé - Deroche, Francine; Simard, Anne (Reflets : Revue ontaroise d'intervention sociale et communautaire, 2007)
Cet article trace les grandes lignes d'un projet de formation à distance qui a été mis en oeuvre en Ontario français. Plusieurs leçons ont été tirées de cette expérience qui peuvent servir dans la planification de futures activités de formation.

‘It would be nice if they could give us more language’ – Serving South Africa’s multilingual patient base - Deumert, Ana (Social Science & Medicine, 2010)

Pas de problème: Rapport du comité d'action sur les services de santé en langue française, 1976 - Dubois, Jacques (Ministère de la santé, Ontario, 1976)
Ce rapport est le fruit des travaux du Comité d'action sur les services de santé en langue française, institué par le ministère de la Santé de l'Ontario et officialisé par un arrêté-en-conseil approuvé en février 1975. Le titre "Pas de problème" est choisi parce que selon le comité, il "résume assez bien la réponse des resposnables de services de santé qui n'ont pas encore perçu les besoins d'un groupe linguistique minoritaire. Pas de problème. Cette simplification d'une situation pourtant très complexe dénote sans doute l'attitude que rencontre trop souvent la population française de l'Ontario." Après une brève recension d'écrits (majoritairement américains) sur les barrières linguistiques en santé, le rapport fait un état des lieux en Ontario à cette époque et énonce plus d'une centaine de recommandations.

Case studies: Primary health service delivery models for the Francophone minority - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
In several regions of the province, Francophones are in a minority situation. In several places, health services in French are minimal or even non-existent. Many stakeholders are trying to find solutions to improve or implement health services in French. Often these solutions are not always easy to identify or put in place. In this context, the Erie St. Clair/SouthWest French Language Health Planning Entity has used the services of a consultant who did an analysis of best practices in minority situations across North America and in other countries. This first analysis consists of a brief description of 352 practices developed to meet the needs of minority populations receiving few, if any, health services in their communities. Following this report, we have continued this research jointly with the Waterloo Wellington, Hamilton, Niagara, Haldimand Brant Entity2 and the French Health Network of Central Southwestern Ontario. Our purpose was to be able to identify 5 or 6 best practices in minority situations that might be applicable in our respective regions under the subject areas: primary health care, seniors care, mental illness and chronic disease. Each of the partners could study identified practices and ask more detailed explanations on certain practices that seemed more appropriate to respond to their local needs.
pages:

Études de cas sur les modèles de livraison de services de santé primaire pour les francophones en situation minoritaire - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
pages: 98

Vers des soins pour toustes. Collectif LGBTQ* du Manitoba et Université de Saint-Boniface (USB). - F.Giguère, Maxe; de Moissac, Danielle; Rokhaya Gueye, Ndeye (2026)
pages: 78

Guide de fonctionnement du système de santé à Terre-Neuve-et-Labrador - Fédération des francophones de Terre-Neuve et du Labrador (FFTNL) (2025)
Déménager dans un nouveau pays et tenter de s’intégrer dans sa nouvelle communauté peut être très stressant. Dans ce contexte, naviguer le système de santé peut représenter des défis particuliers pour les nouveaux arrivants qui choisissent de s’installer à Terre-Neuve-et-Labrador. L’objectif de ce guide est donc de faciliter la compréhension du système de santé de la province pour les nouveaux arrivants. il propose certaines ressources spécifiques pour les francophones.
pages: 32

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Statistique Canada, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Statistics Canada, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)
site internet de Research in focus: https://www.cranhr.ca/focus

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Un meilleur accès en Alberta aux services de santé primaires en français par l'intermédiaire des Primary Care Networks - Gauthier, Hubert; Benomar, Nadia (Réseau Santé Albertain, 2015)
pages: 28

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

La langue au coeur de l’expérience des francophones en santé au Nouveau-Brunswick : étude exploratoire des expériences de la discordance linguistique en santé - Hébert, Shayna-Eve; Violette, Isabelle; Forgues, Éric; Erazo, Atilio; MacLeod, Krystal Kehoe (Minorités linguistiques et société, 2026)
Dans cette étude qualitative exploratoire, nous examinons les expériences de discordance linguistique rapportées par 12 francophones du Nouveau-Brunswick (Canada), province dans laquelle le français est une langue officielle, mais en situation minoritaire. En nous basant sur des entretiens semi-dirigés, nous cherchons à comprendre les expériences de discordance linguistique vécues par la patientèle au sein de cliniques et d’hôpitaux publics faisant partie des réseaux de santé Horizon et Vitalité. L’analyse de contenu thématique (Paillé et Mucchielli, 2021) des récits des patients et des patientes révèle trois types de discordance linguistique auxquels sont liés de multiples effets et émotions chez les participantes et les participants ainsi que des préoccupations à l’égard des droits linguistiques de la minorité francophone. Nous proposons, pour conclure, des pistes pour poursuivre les recherches dans le domaine de la discordance linguistique et pour faciliter l’accès aux services de santé en français dans cette province. In this exploratory qualitative study, we examine experiences of language discordance reported by 12 Francophones in New Brunswick (Canada), a province in which French is an official language but remains minoritized. Drawing on semi-structured interviews, we seek to understand patients’ experiences of linguistic discordance within public clinics and hospitals of the Horizon and Vitalité health networks. A thematic content analysis (Paillé & Mucchielli, 2021) of participants’ accounts reveals three types of linguistic discordance, associated with a range of effects and emotions among participants, as well as concerns regarding the linguistic rights of the Francophone minority. We conclude by proposing directions for future research on linguistic discordance and for improving access to French-language health services in this province.

Welsh Speakers’ Experiences of Health and Social Care Services - IAITH: Welsh Centre for Language Planning for the Department for Health, Social Services and Children (Welsh Government and the Care Council for Wales, 2012)
Nombre de pages: 73

Practice # 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)
fs-ref-orig: Ibrahim, N., Benoît, J. & Savard, J. (2025). Practice 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_ innovative_practices.html fs-code-orig: Ibrahim-2025

Pratique # 28: Accès aux ressources communautaires (ARC) : Un modèle de prescription sociale et de navigation (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Bien qu'il existe de nombreux services et programmes communautaires destinés à répondre aux besoins sociaux et de santé de la population, beaucoup de patients, patientes et médecins généralistes ignorent leur existence, ou peinent à s'y retrouver dnas la multitudes programmes existant. Le modèle ARC est intégré aux soins primaires afin d'aider les patient·es à accéder aux ressources disponibles pour répondre à leurs besoins sociaux et de santé non satisfaits. Cette approche prévoit un point d'entrée unique pour les besoins en santé (non médicaux) et sociaux, amène des changements dans les pratiques afin d'aider les prestataires de soins primaires à mobiliser leur patientèle dans la prise en charge autonome de ces besoins, et fait appel aux services d’un·e navigateur·trice communautaire non clinique, chargé d’accompagner les patient·es dans l’accès aux ressources communautaires appropriées. Parmi les caractéristiques du modèle, on retrouve un acompagnement linguistique bilingue : Les navigateurs et navigatrices ARC sont formés pour offrir un soutien linguistique en français et en anglais pour répondre aux besoins des patient·es, adoptent une approche d’« offre active » et veillent à ce que les patient·es puissent accéder facilement et confortablement aux services et à l’information dans la langue de leur choix.

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Résumé Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. Abstract Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

Language as a barrier to care for Xhosa-speaking patients at a South African paediatric teaching hospital - Levin, M. E. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Disease is closely linked to the social context in which we live. Difficulty with communication, cultural incompatibility between patients and health care providers and socioeconomic obstacles are important barriers to quality care when doctors and patients come from different backgrounds and speak different languages. Red Cross War Memorial Children's Hospital (RCH) is a paediatric teaching hospital in Cape Town where staff members communicate mainly in English or Afrikaans, while many patients speak Xhosa as their first language. OBJECTIVES: The study aimed to identify barriers to optimal care for Xhosa-speaking parents of patients at RCH. The contribution of language difficulties was assessed as a possible barrier to health care for this group. DESIGN: A questionnaire was developed and administered to 53 Xhosa-speaking parents of children admitted to the short-stay ward at RCH. The questionnaire examined parents' perceptions of barriers to their children's care, using openended questions, closed-ended questions and selection from lists. RESULTS: Parents experienced significant structural and socioeconomic barriers to access of health care for their children. Language and cultural barriers were cited by more parents as a major barrier to health care than structural and socioeconomic barriers. Parents did not have access to same-language practitioners, as only 6% of medical interviews were conducted partly or wholly in the patient's home language. Of the 94% of interviews where no Xhosa was spoken by medical staff, 21% were conducted with the aid of an interpreter (formal or ad hoc) and in 79% no interpreter was used. Parents experienced difficulties with understanding the doctors (64%), making themselves understood (54%) and asking questions (38%). Sixty-nine per cent of parents were dissatisfied with communication between themselves and their doctors and 45% were concerned about negative effects of poor communication on them or their children. Parents tended to blame their own linguistic limitation rather than those of the doctors.
Keywords: Adolescent; Adult; Communication Barriers; Cultural Characteristics; Health Care Surveys; Health Services Accessibility; Hospitals; Pediatric; Hospitals; Teaching; Humans; Language; Middle Aged; Multilingualism; South Africa

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.
Nombres de pages: 85

Official Language Minority Communities in Ontario: (In)visibility of Nursing Care - Muray, Mwali; Chartrand, Julie; Perron, Amélie (Aporia, 2026)
Despite Canada’s linguistic duality, French-speaking minority populations continue to face significant barriers in accessing equitable health care. Investigating two key research questions, this study explores: (1) What are the lived experiences of registered nurses and nursing students caring for French-speaking patients in Ontario? and (2) How do French-speaking patients navigate the health care system to access care in their preferred language? Using qualitative methodology informed by interpretive phenomenology, 31 participants were interviewed individually between 2018 and 2019, offering firsthand accounts of their experiences. Findings reveal a paradox of (in)visibility: French-speaking patients and nursing providers remain invisible when they adapt to systemic shortcomings but become highly visible when they advocate for equitable care. The study highlights the urgent need for the effective and consistent implementation of the strategic changes within health care institutions. Addressing these linguistic disparities is not only a matter of patient safety and quality care but also a fundamental step toward upholding Canada’s bilingual commitments in health service delivery.

Santé des organismes communautaires inc. - Nolet, Lise (Reflets, 1999)
Cet article décrit la création et le mandat de Santé des organismes communautaires inc. (SOCI), un nouvel organisme à but non-lucratif qui a été créé pour administrer le programme de révisions et d’accréditation des Centres de santé communautaires (CSC) en Ontario. Il existait, au moment de sa création, 54 CSC en Ontario, dont cinq qui offraient uniquement des services en français.

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Partenariat communauté en santé (PCS): Le réseau pour la santé en français au Yukon - Partenariat communauté en santé
Ce document offre de l'information en français sur les services de santé de première ligne au yukon et sur les services disponibles en français.
Nombre de pages : 3

Cinq façon d'aider.. Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Five ways to support... Francophone patients - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

The Impact of Communication Challenges on the Delivery of Quality Health Care to Minority Clients & Communities - PEI French Language Health Services Network; Société Santé en français (2007)
pages: 69

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Ce rapport présente les principaux résultats de l’Enquête sur la population de langue officielle en situation minoritaire (EPLOSM) de 2022. Il brosse un portrait d’ensemble de la situation des populations de langue anglaise au Québec et de langue française dans les autres provinces et les capitales des territoires du Canada. Cette enquête a été menée afin de mieux comprendre la situation des personnes de langue officielle en situation minoritaire en ce qui concerne certains sujets et enjeux actuels, comme la scolarité, les services à la petite enfance, l’accès à d’autres services dans la langue officielle minoritaire et leur utilisation, ainsi que les pratiques linguistiques à la maison, au travail et dans l’espace public. L’enquête, qui représente une collaboration entre Statistique Canada et Patrimoine canadien, vise à soutenir les utilisateurs de données sur les communautés de langue officielle en situation minoritaire. L’Enquête sur la population de langue officielle en situation minoritaire de 2022 est une enquête postcensitaire, c’est‐à‐dire que son échantillon provient du Recensement de la population de 2021. La population de langue officielle en situation minoritaire désigne la population de langue anglaise au Québec et la population de langue française au Canada hors du Québec. L’enquête a été menée dans les 10 provinces canadiennes du 16 mai au 16 décembre 2022, ainsi que dans les capitales des trois territoires canadiens du 22 août au 16 décembre 2022. Au total, près de 30 000 personnes y ont répondu. L’échantillon des adultes comprend 13 892 répondants, alors que l’échantillon des enfants compte 16 066 enfants pour lesquels un parent ou un tuteur a répondu à certaines questions portant sur leur enfant et à d’autres portant sur eux‐mêmes.
Nombre de pages: 40

Étude de besoins préalable à l’adaptation de la formation en offre active de services en français au secteur de la santé et des services sociaux - PGF pour Fédération franco-ténoise, Réseau TNO Santé et le gouvernement des Territoires du Nord-Ouest (2019)
Nombre de pages: 34

Examining the impact of two patient navigation models within a social prescribing program on self-reported health service utilization and health-related quality of life (Doctoral dissertation, Laurentian University Library & Archives) - Pitre, Joël (2025)
Abstract Background: Social prescribing programs have shown promise for addressing the healthcare system fragmentation and the negative impact of certain social determinants of health. They entail primary care providers referring patients with unmet health or social needs to community resources, a process that is mediated by a lay navigator, who assists patients in identifying barriers and facilitating access to the appropriate resources. Although Ontario 211 and the Access to Resources in the Community (ARC) intervention both utilize lay navigators to assist their patients, the former provides informational services to its patients, whereas the latter offers more comprehensive and reoccurring support to patients. Study Objective: This study compared the impact of both navigation models within a social prescribing program setting on patient self-reported health service utilization and health-related quality of life. Methods: A secondary analysis was conducted using data collected in 2018/19 during the randomized control trial (RCT) comparing ARC and Ontario 211 navigation. Three hundred and twenty-six patients were enrolled in the study, and 237 patients completed the post-intervention questionnaire. Participants were adults who had identified an unmet health or social need and frequented a primary care provider. Health service utilization outcomes included the number of emergency department (ED) visits and hospitalizations, while the health-related quality of life was assessed with the validated Veterans RAND 12 questionnaire. Unadjusted and adjusted regression analyses were conducted to compare outcomes between both navigation models, controlling for socio-demographic characteristics. Results: Although none of the results reached statistical significance, participants assigned to the ARC navigation intervention had an apparent higher odds of ED visits and modestly improved physical quality of life yet had relatively similar odds of hospitalization and improvement in mental quality of life compared to those in the Ontario 211 arm. Conclusion: Despite not demonstrating statistically significant associations, the results provide insight into the emerging field of social prescribing in Canada. In today’s political and economic landscape, with a healthcare system focused on addressing social determinants of health, there remains an ongoing need for innovative evaluations of preventative interventions. While effects may not always be observed immediately, as in these findings, with continued research, social prescribing programs show potential for leading the way to equitable care. Keywords: Social prescribing, emergency department, hospitalization, health-related quality of life, patient navigation
pages: 117

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance: Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective : To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures: Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care. Main Outcomes and Measures MACEs within 5 years of survey completion. Results : Among the 124 583 patients included in this study, 114 239 (91.7%) spoke English, 4790 (3.8%) spoke French, 325 (0.3%) spoke an Indigenous language, and 5229 (4.2%) spoke an allophone (ie, other) language. The mean (SD) age of the cohort was 63.7 (14.8) years; 57.1% of the patients reported their sex as female. Very few respondents who spoke an Indigenous language at home (<4.6%) received language-concordant care. For French-speaking patients, there was no statistically significant difference in the risk of MACE between those who received language-concordant care and those who received language-discordant care (hazard ratio [HR], 1.09; 95% CI, 0.86-1.36). Allophone-speaking patients who received language-concordant care were 36% less likely to experience MACE (HR, 0.64; 95% CI, 0.51–0.80) compared with allophone-speaking patients who received language-discordant care. Conclusions and Relevance: This retrospective cohort study found large disparities in both access to language-concordant care and risk of MACEs. These findings suggest that language-concordant care could potentially improve the health of individuals in minority language communities.

Joint Position Statement on the Linguistic Variable - Regroupement des Entités de planification des services de santé en français de l'Ontario (2013)
pages: 7

Amélioration de l’expérience des francophones dans les soins de santé – Rapport final - Réseau du mieux-être francophone du Nord de l'Ontario (2021)
En 2018, le Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) a obtenu des fonds afin de mener un projet portant sur l’expérience des francophones et, plus précisément, sur son amélioration en matière de services de santé en français dans la région du Nord de l’Ontario. Dans le contexte du projet, nous avons recueilli des expériences de patients francophones dans le but de valider les besoins qui ont souvent été identifiés par les francophones sur l’accès et l’équité des services de santé en français. Ces données nous ont permis de créer des ressources pour mieux outiller les fournisseurs de services de santé dans l'offre de soins culturellement adaptés. Ce document consiste en un sommaire des résultats obtenus à la suite des rencontres et des échanges avec des francophones de différentes régions du Nord de l’Ontario ainsi que des pistes de solution, des outils et des ressources pour appuyer les fournisseurs de services de santé à améliorer l’offre active de services de santé en français.
Nombre de pages: 8

Improving the Francophone Experience in Healthcare – Final Report - Réseau du mieux-être francophone du Nord de l'Ontario (2021)
Number of pages: 8

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Guide santé pour les nouveaux arrivants en Nouvelle-Écosse - Réseau santé en Nouvelle-Écosse, Immigration francophone Nouvelle-Écosse et Réseau en immigration francophone de la Nouvelle-Écosse (2022)
pages: 76

Guide santé pour les nouveaux arrivants aux territoires du Nord-Ouest - Réseau TNO Santé (2022)
pages: 80

Passeport santé pour les nouveaux arrivants aux Territoires du Nord-Ouest - Réseau TNO Santé (2022)

Language related difficulties experienced by caregivers of English-speaking seniors in Quebec - Sanderson, Duncan (SAGE Open, 2020)
Little research has examined communication problems between speakers of official minority languages (patients or caregivers) and health care providers. The objective of this research was to identify the types of issues experienced by English-speaking caregivers of seniors in Quebec, as they interact with French-speaking health care providers. The majority of the caregivers interviewed indicated that they were satisfied with physicians’ interaction with the seniors they cared for. However, problems included health care providers who do not or who refuse to speak English, hospice personnel with insufficient English, anxiety about speaking to personnel in French, traveling to receive services in English, acting as an informal interpreter, receiving written documents in French, scheduling appointments through French-only phone systems or receptionists, and discrimination. The main finding is that in Quebec, language asymmetry might create additional stresses for an English-speaking caregiver, who is already likely to be stressed because of their caregiver role.

Trousse d’accompagnement pour l’examen médical du nouvel arrivant - Sanou, Baroma; Gauthier, Alain; Chomienne, Marie-Hélène; Prud'homme, D.; Kpazaï, G. (2018)
fs-ref-orig: Sanou, B., Gauthier, A., Chomienne, M.-H., Prud'homme, D. et Kpazaï, G. (2018). Trousse d’accompagnement pour l’examen médical du nouvel arrivant. Centre de recherche en santé dans les milieux ruraux et du nord, Institut du Savoir Montfort et Centre de la santé communautaire du Grand Sudbury. fs-code-orig: Sanou-2018

Guide de navigation du réseau de la santé et des services sociaux du Manitoba - Santé en français Manitoba (2024)
L’élaboration du présent guide visait à faciliter le cheminement des gens dans le réseau manitobain de la santé. Il se veut un outil pratique permettant aux personnes francophones de s’orienter rapidement dans le réseau de la santé. Les nouveaux arrivants, les voyageurs ou les résidents de longue date aux prises avec un nouveau problème de santé ont souvent beaucoup de questions à poser et un grand besoin d’aide pour trouver les bonnes ressources dans le réseau. Compte tenu de sa mission d’améliorer l’accès à des services de santé et des services sociaux d’excellente qualité en français, Santé en français a collaboré avec le Réseau en immigration francophone (RIF) du Manitoba pour élaborer le présent guide avec en tête les objectifs suivants : • Aider les gens à comprendre le réseau manitobain de la santé. • Faire connaître les principales coordonnées et les voies d’accès, et renseigner sur la façon d’accéder aux services publics et à certains services privés.
Nombre de pages: 56

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Saulnier, Gaston; Roisné, Pierre (Réseau santé en français-Nouvelle-Écosse, Santé Nouvelle-Écosse, 2021)
En 2009, le Réseau Santé – Nouvelle-Écosse a mené une série de consultations auprès des communautés acadiennes et francophones partout en Nouvelle-Écosse, qui ont abouti à 31 recommandations (disponibles ici : reseausantene.ca/rapports/) En2018, on souhaitait uen mise à jour de la situation. Désireux de venir rencontrer les partenaires clés dans le milieu de la santé des différentes communautés acadiennes et francophones, Katherine Howlett, consultante en services en français à Santé Nouvelle-Écosse, remplacée par la suite par Gaston Saulnier, et Pierre Roisné, nouveau directeur général du Réseau Santé – Nouvelle-Écosse, ont tenu une série de rencontres en mars et novembre 2019, dans le Sud Ouest, le Nord-Est puis la région centrale de la Nouvelle-Écosse. La pandémie COVID-19 a suspendu ces consultations qui se sont achevées en novembre 2020 par une consultation en ligne pour la région Halifax. Les objectifs de ces rencontres étaient à la fois d’entendre les enjeux liés à l’accès en français aux services de santé dans les différentes communautés, mais également d’entendre les partenaires sur des enjeux particuliers tels que l’accès aux services d’interprétation. Ces échanges permettront de mettre à jour les recommandations issues des rencontres tenues 10 ans plus tôt et proposer de nouvelles pistes d’actions. Les recommandations finales de ce rapport sont issues des discussions avec les partenaires et elles viendront s'ajouter aux autres priorités identifiées par les organismes dans leur planification stratégique (promotion de la santé, formation, petite enfance...). Le rapport s’ouvre sur les enjeux transversaux mentionnés aux différentes rencontres, et se poursuit par la présentation des enjeux propres à chacune des communautés. Le rapport présente ce qui a été entendu lors de ces rencontres. Il ne constitue pas les points du vue officiels de Santé Nouvelle-Écosse ou du Réseau Santé Nouvelle-Écosse.
Nombre de pages: 27

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Tous les organismes qui souhaitent offrir des services en français n’ont pas nécessairement les ressources nécessaires pour le faire. Les points de service satellites francophones constituent des ententes formelles par lesquelles des intervenant·es ou des professionnel·les de services sociaux et de santé d’un organisme offrent des services dans les locaux d’un autre organisme, dans le but de mieux servir les personnes âgées francophones. Les services offerts varient selon les besoins décelés par l’organisme hôte du service satellite, ainsi que les ressources disponibles (financières, main-d’œuvre) de la part de l’organisme fournissant le service.
Note: En 2025, ce document a fait l'objet d'une mise à jour du format, sans changement au contenu. fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 10 : Les points de service satellites (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021d

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Le quartier de Vanier, situé à l’est de la rivière Rideau, dans la ville d’Ottawa, abrite un grand nombre des personnes aînées francophones. Toutefois, une carence de services offerts en français et des conditions socioéconomiques précaires constituent des réalités qui tendent à vulnérabiliser la population. Les Lunchs-causeries du CSC Vanier Les lunchs-causeries ont vu le jour en 2009 grâce à une collaboration entre divers acteurs du milieu. Il s'agit de rencontres mensuelles qui visaient à briser l’isolement ainsi qu’à informer et outiller les personnes aînées de deux immeubles subventionnés pour personnes âgées dans le quartier Vanier, en vue d’accroître leur qualité de vie. Ils constituaient une occasion de construire un lien de confiance entre la personne aînée et l’intervenant·e du CSC Vanier Divers défis, dont ceux de son financement, font qu'en 2025, la pratique n'était plus mise en oeuvre.
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025g

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Ce programme, financé par Santé publique Ottawa, permettait le déploiement d’une infirmière de cet organisme dans le Centre de services communautaires (CSC) Vanier, qui dessert une communauté d'ainés majoritairement francophone. Son rôle était d’identifier les besoins des personnes aînées et de faire l’aiguillage de ces personnes vers les services dont elles avaient besoin. Tout comme l’ont fait les intervenant·es psychosociaux du CSC Vanier, l’infirmière de Santé publique Ottawa a pu utiliser la porte des Lunchs-causeries (voir pratique #12) pour rejoindre les résident·es dans leur milieu de vie et aborder leurs préoccupations de santé. L’infirmière pouvait ainsi aider à la gestion des médicaments et faire de l’aiguillage vers les services de santé de niveau de soins appropriés, dans le but de réduire les visites non nécessaires aux urgences des hôpitaux. Divers défis, dont ceux de son financement, que la pratique n'a pas pu être perrénisée.
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Savard-2025h

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Les foires d’information sont des évènements annuels qui visent à nformer les personnes aînées francophones dans leur langue, sur divers sujets qui peuvent avoir une incidence sur leur qualité de vie. De plus, les foires d’information constituent des plateformes de réseautage et une occasion de créer ou de renouveler des partenariats pour les organisations participantes. Les foires d’information permettent aux aînés francophones de mieux connaître les services disponibles en français, et aux organisations, de mieux connaître les besoins de la population aînée francophone.

Pratique # 4 : L’intégration de la variable linguistique dans la collecte de données (Île-du-PrinceÉdouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
L’identité linguistique des usager·ères du système de santé de l’Î.-P.-É. a été recueillie par le biais de sondages envoyés entre octobre 2015 et janvier 2017 à 58 000 foyers (124 000 personnes). Les résultats ont montré que 4,4 % des répondant·es ont déclaré le français comme langue maternelle. À la suite de cette enquête, l’Î.-P.-É. a établi une nouvelle carte-santé bilingue qui permet de relier automatiquement le profil linguistique de l’usager·ère aux bases de données utilisées par les professionnel·les de la santé. Cette carte permet également de retracer l’utilisation antérieure des services de santé. Pour les usager·ères, c’est une façon appropriée de suggérer une demande de services en français sans avoir besoin de le faire verbalement à chaque point de services. Les résultats de cette initiative démontrent la faisabilité de lier ces données aux bases de données provinciales, permettant un accès rapide et sécuritaire au profil linguistique des usager·ères par les professionnel·les de la santé et des planificateur·ices des services.
Mot clé: carte santé Note: En 2025, ce document a fait l'objet d'une mise à jour du format, sans changement au contenu.

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Le programme de Soins primaires communautaires pour aînés soutient les aînés et leurs proches aidants dans l’accès aux services sociaux et de santé requis (par exemple, la sécurité alimentaire, le logement, le revenu, le règlement, les services de soutien à domicile, le transport, l’éducation en matière des maladies chroniques, les activités sociales, physiques et récréatives). Un ou une gestionnaire de cas (soit un infirmier, infirmière ou un·e agen·te de santé communautaire) coordonne les services et les supports nécessaires et clarifie les rôles des fournisseurs de soins, facilitant ainsi la transition vers d’autres services. Il ou elle élabore, surveille et appuie la mise en œuvre des plans de soins coordonnés, et ce, dans un contexte de continuité relationnelle intervenant·e-client·e. Le service est offert en français et en anglais dans plusieurs centres de santé communautaires de la région d’Ottawa. Par la gestion de cas et la navigation des services, le programme facilite l’accès aux services en français qui existent.
Note: En 2025, ce document a fait l'objet d'une mise à jour du format, sans changement au contenu. fs-ref-orig: Savard, J., Savard, S., Van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019). Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/cahier_de_pratiques.html fs-code-orig: Savard-2019c

The effects of a language barrier in a South African district hospital - Schlemmer, A.; Mash, B. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Communication between health workers and patients at Hottentots Holland Hospital (HHH) is hindered by staff and patients not speaking the same language. HHH is a district hospital in the Cape Town Metropolitan District of the Western Cape where staff mainly speak Afrikaans or English and a large number of patients mainly Xhosa. OBJECTIVES: The study aimed to explore the effects of this language barrier on health workers and patients at HHH. DESIGN: Three focus group interviews were held with 21 members of staff and 5 in-depth patient interviews were conducted. RESULTS: The language barrier was found to interfere with working efficiently, create uncertainty about the accuracy of interpretation, be enhanced by a lack of education or training, cause significant ethical dilemmas, negatively influence the attitudes of patients and staff towards each other, decrease the quality of and satisfaction with care, and cause cross-cultural misunderstandings. CONCLUSION: The effects of the language barrier were considerable and persistent despite an official language policy in the province. The training and employment of professional interpreters as well as teaching of basic Xhosa to staff are recommended.
Keywords: Communication Barriers; Health Services Accessibility; Hospitals; District; Humans; Language; Multilingualism; Outcome Assessment; Health Care; Professional-Patient Relations; South Africa; Surveys and Questionnaires

Active Offer of French-Language Health Services for Francophone and Acadian Minority Communities in Canada - Joint position statement - Société Santé en français (2017)
pages: 10

L'offre active des services de santé en français dans les communautés francophones et acadienne en situation minoritaire au Canada - Énoncé de position commune - Société Santé en français (2017)
pages: 10

Delivery of Health Care Services in Both Official Languages: Let's see to it! - Société Santé et mieux-être du Nouveau- Brunswick (2009)
pages: 8

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society / Minorités linguistiques et société, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Distance, accès et équité : une analyse géospatiale transversale des inégalités dans l'accès aux soins primaires pour les francophones seulement à Ottawa, Ontario - L'essentiel - Unité de soutien de la SRAP de l'Ontario - Initiative francophone
Ce sommaire de recherche présente les principaux résultats de l'étude suivante: Belanger et al. (2023). Distance, access and equity: a cross-sectional goespatial analysis of disparities in access to primary care for French-only speakers in Ottawa, Ontario. CMAJ Open, 11(3), E434-E442.

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Le Centre francophone du Grand Toronto (CFGT ou le Centre) est la porte d’entrée pour les francophones qui vivent à Toronto ou qui s’y installent. Le Centre est un organisme sans but lucratif qui compte plusieurs points se services et offre une gamme diversifiée de services communautaires de santé, de services sociaux et d’accès au logement à l’ensemble de la communauté francophone du Grand Toronto. L’objectif du projet était la création d’un système d’enregistrement des usagers et usagères du Centre qui facilite l’accès à tous les services en une seule demande grâce à un formulaire en ligne ; l’uniformisation des pratiques d’accueil et des informations demandées aux clients, la centralisation de l’information sociodémographique pour mieux coordonner la collecte des données et l’aiguillage vers les services appropriés pour la clientèle. L’accueil centralisé facilite la collecte des données sociodémographiques des usager·ères (évite les répétitions), permet un aiguillage plus rapide et efficace, tout en répondant mieux aux demandes de bailleurs de fonds. Le système permet de centraliser l’information sur les services sollicités et leur provenance parmi plusieurs points de services, informations qui peuvent être utilisées pour la conception et la mise en place de nouveaux programmes.
fs-ref-orig: van Kemenade, S., Benoît, J., Savard, S. et Savard, J. (2025). Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html. fs-code-orig: van Kemenade-2025d

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Le Navigateur francophone du système de santé (NFSS) était un projet pilote, mis en place en 2021, qui cherchait à fournir un niveau supplémentaire de soutien aux patient·es et aux familles francophones afin de faciliter leur navigation du système de santé et leur accès aux services. Le NFSS avait pour objectif d’améliorer l’accès aux services de santé pour les communautés francophones et acadiennes de T.-N.-L. et de fournir des informations aux fournisseurs de soins de santé, lorsqu’ils devaient orienter leurs patient·es vers des services en français. Une infirmière autorisée a été embauchée à temps partiel pour le poste de NFSS; elle travaillait en étroite collaboration avec les patient·es, les familles et d’autres clinicien·nes et partenaires communautaires pour fournir aux francophones les informations nécessaires pour prendre les meilleures décisions de soins. Malgré un coût somme toute minime, le financement du projet n'a pas été reconduit après 2021.
fs-ref-orig: van Kemenade, S., Michel, J.N., Savard, J. & Benoît, J. (2021, mise à jour 2025). Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: van Kemenade-2025a

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.

My language, my health: The Welsh Language Commissioner’s inquiry into the Welsh language in primary care. - Welsh Language Commissioner (2014)

Bottin des ressources en petite enfance à Iqaluit, Nunavut - youth primary health care (2020)
Ce bottin vise à aider les parents de jeunes enfants et les intervenants à avoir accès rapidement aux ressources pertinentes à la petite enfance qui sont disponibles à Iqaluit. Ce bottin présente une recension exhaustive de ces ressources en spécifiant le niveau d’accès aux services en français. Par ressources, on entend ici les services, les programmes, les ressources éducatives et autres sources d’information pertinente pour les périodes pré et péri natales, ainsi que pour les familles avec enfants de 0 à 6 ans.